Phadebact Monoclonal GC OMNI Test for confirmation of Neisseria gonorrhoeae. - Carlson, B L (1987)
The Phadebact Monoclonal GC OMNI Test (Pharmacia Diagnostics, Piscataway, N.J.) is used for the definitive identification of Neisseria gonorrhoeae. In this test, boiled organisms are examined by using a 1-min coagglutination technique. A total of 776 Neisseria strains, confirmed to the species level by patterns of acid production from carbohydrates incorporated in cysteine-tryptose agar or morphologically consistent with Neisseria meningitidis and fluorescent antibody negative, were tested by the coagglutination technique. Of the 516 isolates of N. gonorrhoeae, 8 (1.6%) were negative with the OMNI Test. Of the 260 isolates of Neisseria spp. other than N. gonorrhoeae, none showed a positive coagglutination reaction. The Phadebact Monoclonal GC OMNI Test provided rapid, accurate identification of N. gonorrhoeae (sensitivity, 98.4%; specificity, 100%).